Muslim heritage and environment: the case of the watchtowers of the nasrid kingdom of Granada (thirteenth to fifteenth century) - García-Pulido, Luis José; Ruiz-Jaramillo, Jonathan (My University, 2018)
This paper is devoted to the study of the different towers of the Nasrid kingdom of Granada (1232 to 1492) and their linked landscapes, as well as the evolution, preservation, resilience or transformation of their environment until present days. These late Islamic territories in medieval Iberia occupied the mountainous areas of the southeastern area of today’s Spain. There, a natural border was established between the Nasrid kingdom and the expansion of Castile during more than two centuries and a half. To control this frontier and establish visual communication between it and the Nasrid power centres lead by the Alhambra citadel, an extensive network of watchtowers and defensive towers linked to farmsteads was constructed. These towers are located in unique sites; being erected as reference landmarks of the territories on which they stand. These fortifications, with very diverse typology and morphology, are a faithful testimony to the different territorial structure that has taken place throughout history.
Luis José García-Pulido y Jonathan Ruiz-Jaramillo. “Muslim heritage and environment: the case of the watchtowers of the nasrid kingdom of Granada (thirteenth to fifteenth century)”. En: Heritage 2018. Proceedings of the 6th International Conference on Heritage and Sustainable Development (10th Anniversary Edition) Granada, Spain, 12-15 June 2018. Edited by Rogério Amoêda, Sérgio Lira, Cristina Pinheiro, Juan M. Santiago Zaragoza, Julio Calvo Serrano, Fabián García Carrillo. Editorial Universidad de Granada y Green Lines Institute for Sustainable Development, Granada, 2018. e-ISBN 978-84-338-6261-7
Keywords: Torres vigía - Málaga (Provincia); Medieval military architecture; The Islamic Nasrid Kingdom of Granada; Watchtowers and defensive towers